A Wrestler’s Nightmare: Pectoralis Major Tendon Tear and its Repair-A Case Report - Maulik Kothari; Rajendra Phunde; Kumar Parth; Sourav Kumar; Surendar Singh Bava; Rohit Somani (Journal of Orthopaedic Case Reports)
Introduction: Pectoralis major tendon (PMT) tears are increasingly common, particularly among young, athletic individuals. Case Report: This case report discusses the management of a chronic PMT tear in a 24-year-old professional wrestler who sustained an injury during a wrestling match. Initially treated conservatively with immobilization and physiotherapy, the patient presented 1 year later with unsatisfactory functional outcomes. Clinical examination and imaging confirmed the retracted tendon, leading to a decision for surgical repair. An open repair of the PMT was performed using a standard clavipectoral approach with suture anchors to reattach the tendon to its anatomical insertion on the humerus. Post-operative rehabilitation focused on progressive range of motion and strength training, enabling the patient to return to pre-injury levels of athletic performance after 8 months. Conclusion: The results highlight the importance of early diagnosis, prompt surgical intervention, and a structured rehabilitation plan in achieving optimal functional and cosmetic outcomes in young athletes with chronic PMT tears.